Sharia Fintech Securities Crowdfunding (SCF) Business Model - Budi Prasetyo, Rifqi; Rahadian, Dadan; Krisnawati, Astrie (International Journal of Science, Technology & Management, 2025)
The growth of the sharia economy, especially in the Securities Crowdfunding (SCF) sector, is increasingly in demand because it offers a fair financial concept. This great potential encourages startups to establish sharia-based SCF companies, such as LBS Urun Dana. However, the main challenge is the lack of public understanding of the sharia SCF business model, which often creates negative perceptions, especially among MSMEs and investors. This study aims to describe the LBS Urun Dana business model using the Business Model Canvas and Value Design Model approaches, and to analyze the strengths of sharia SCF as a driver of industrial growth in Indonesia. The method used is qualitative with data collection techniques through interviews and documentation, as well as descriptive and SWOT analysis. The results of the study show that LBS Urun Dana has integrated sharia principles comprehensively, with strong strategic partnerships and effective risk management. The focus on transparency, financial inclusion, and investor education strengthens public trust. Strengths in sharia SCF, such as solid partnership networks and sharia analysis competencies, are identified as the main factors for the growth of the sharia SCF industry in Indonesia.